A STUDY ON AWARENESS AND ACCESS TO FINANCIAL INCLUSION AMONG AGRICULTURAL LABOURERS WITH SPECIAL REFERENCE TO SIVAGANGAI DISTRICT - P. Jayalakshmi, Dr. M.Ganesan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Financial inclusion is new paradigm of economic growth. It plays an important role in driving away the poverty from our nation. It is an integral part of inclusive growth and sustainable development of the nation. The term financial inclusion refers to delivery of financial products and services at an affordable cost in a fair and transparent means to weaker sections of society. Financial inclusion is very useful for the agricultural labourers, who are not aware about financial products and services provided by the financial institution. The study is focused socio economic condition of agricultural labourers and their level of awareness and access to financial inclusion in sivagangai district. Primary data are collected from agricultural labourers by using interview schedule and multi stage random sampling was used for the selection of respondents. The study revealed that the agricultural labourers are aware and access to some extent about financial inclusion product and services only for the enjoying the government benefits and schemes. This work concludes that most of the agricultural labourers are aware and included in the financial inclusion system in terms of access of bank account it does not lead to continues usage of bank account.